Conservação pós-colheita de Bastão-do-imperador - Mattos, Drucylla Guerra (2015)
The use of post-harvest techniques that afford quality and longevity, it is essential for successful marketing of flowers. Thus, the objective was to evaluate the longevity and post-harvest quality of torch ginger flower stems in two floral opening stages using carnauba wax treatment and stored at temperatures of 16° C and 21° C. It was applied different concentrations of carnauba wax (0.0% - control; 0.75%; 1.5%; 3.0%) in combination with two stages of flower opening (semi-open and open bracts), resulting in 8 treatments, which were distributed completely randomized, with 4 repetitions for treatment, in split plot in time. Evaluations were performed every two days during 20 days. It was observed the visual quality through a scale of notes given by three evaluators; besides evaluation of relative fresh weight, water uptake, transpiration and water balance. Bracts were taken for analysis by light microscopy and scanning electron, allowing the verification of the deposition standard of carnauba wax in the bracts. Also, it was taken samples every three days of bracts to determine the levels of total soluble sugars and starch. It was observed that wax is deposited in epicuticular way with plate format. But it was not observed effect of carnauba wax on the physiological aspects or visual quality. In both storage temperatures, the semi-open flower opening stage provided better visual quality for a larger number of days during the storage time evaluated, also physiological responses that contribute to greater post-harvest longevity.